Eternal Russia … The USSR and the RUSSIAN People in the Vision and in the Writings of the Portuguese Jesuit Fr. Manuel Antunes, SJ. (3rd July 2019) - Franco, José Eduardo
ABSTRACT: In this article we present a distillation of Fr. Manuel Antunes's thought, visible in a series of texts that analyse the evolution of the Soviet Union and its ideological-political atheistic system, which kept a 'discordant' relationship with the millenary identity of the Russian people. Antunes's critical view of Russia can be gleaned from many articles published in Brotéria magazine, some of which, due to their prospective character, are still relevant today. In fact, in the 1960s and 1970s, Manuel Antunes knew how to anticipate with unique lucidity the drifts, problems and outcomes that would mark international life. His texts on Russia and the 'Soviet empire' are a good example of this prospective thought, since they identify the difficulties and predict the fall of the Soviet regime, with the foreseeable announcement of a democratic revolution before the year 2000, which would happen with the fall of the Berlin Wall in 1989.